Study of Graphene-Based Materials: Creation, Examination, Characteristics, and Diverse Applications (International Journal of Food and Nutritional Sciences, 2021)
This study delves into the realm of graphene-based materials, with a comprehensive focus on their fabrication, analysis, properties, and multifaceted applications. Graphene, a single layer of carbon atoms arranged in a two-dimensional honeycomb lattice, has garnered immense attention due to its remarkable electrical, mechanical, and thermal properties. Our investigation encompasses the latest advancements in the fabrication techniques of graphene-based materials, shedding light on innovative synthesis methods and their impact on material properties. Through a rigorous analysis, we unravel the unique characteristics and behaviors exhibited by these materials, elucidating their potential in various domains. highlight the diverse and burgeoning applications of graphene-based materials, ranging from electronics and energy storage to nanocomposites and biomedical devices. This study aims to provide a comprehensive understanding of the evolving landscape of graphene-based materials, offering insights into their synthesis, characterization, and the wide spectrum of practical uses, thereby contributing to the ongoing advancement of this transformative field.